Proteomic analysis reveals semaglutide impacts lipogenic protein expression in epididymal adipose tissue of obese mice - Zhu, Ruiyi; Chen, Shuchun (Frontiers in Endocrinology, 2023)
Background and objectives: Obesity is a global health problem with few pharmacologic options. Semaglutide is a glucagon-like peptide-1 (GLP-1) analogue that induces weight loss. Yet, the role of semaglutide in adipose tissue has not yet been examined. The following study investigated the mechanism of semaglutide on lipid metabolism by analyzing proteomics of epididymal white adipose tissue (eWAT) in obese mice. Methods: A total of 36 C57BL/6JC mice were randomly divided into a normal-chow diet group (NCD, n = 12), high-fat diet (HFD, n = 12), and HFD+semaglutide group (Sema, n = 12). Mice in the Sema group were intraperitoneally administered semaglutide, and the HFD group and the NCD group were intraperitoneally administered an equal volume of normal saline. Serum samples were collected to detect fasting blood glucose and blood lipids. The Intraperitoneal glucose tolerance test (IPGTT) was used to measure the blood glucose value at each time point and calculate the area under the glucose curve. Tandem Mass Tag (TMT) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to study the expression of eWAT, while cellular processes, biological processes, corresponding molecular functions, and related network molecular mechanisms were analyzed by bioinformatics. Results: Compared with the model group, the semaglutide-treated mice presented 640 differentially expressed proteins (DEPs), including 292 up-regulated and 348 down-regulated proteins. Bioinformatics analysis showed a reduction of CD36, FABP5, ACSL, ACOX3, PLIN2, ANGPTL4, LPL, MGLL, AQP7, and PDK4 involved in the lipid metabolism in the Sema group accompanied by a decrease in visceral fat accumulation, blood lipids, and improvement in glucose intolerance. Conclusion: Semaglutide can effectively reduce visceral fat and blood lipids and improve glucose metabolism in obese mice. Semaglutide treatment might have beneficial effects on adipose tissues through the regulation of lipid uptake, lipid storage, and lipolysis in white adipose tissue.